The effects of cognitive learning and imagination training on the balances of the 14-16 years old handball players - Turan, M. B.; Disçeken, O. (Journal of Education and Training Studies, 2019)
The purpose of this research is to examine the effects of imagination and cognitive learning exercises, which are applied to increase the success of elite handball players, on their balance skills.